Negative feedback control of exocrine pancreatic secretion: role of cholecystokinin and cholinergic pathway - Owyang, C. (University of Michigan Medical Center, Ann Arbor, MI.) (The Journal of nutrition, 1994)
Mediation of postprandial pancreatic enzyme secretion has been ascribed mainly to cholecystokinin and to vagovagal reflexes. Recent studies suggest that these pathways are subject to feedback regulation. Diversion of pancreatic juice from the duodenum stimulates cholecystokinin release and pancreatic enzyme secretion, and intraduodenal administration of trypsin or chymotrypsin inhibits cholecystokinin release and pancreatic secretion. The increased plasma cholecystokinin levels following diversion of pancreatic juice seems to be mediated by "cholecystokinin-releasing factor", a trypsin-sensitive substance secreted by the proximal small intestine. This factor may mediate pancreatic enzyme secretion in response to protein intake. Dietary protein in the intestine competes for the trypsin that would otherwise inactivate the factor. The resulting increase of this factor in the intestinal lumen releases cholecystokinin and stimulates pancreatic enzyme secretion. Enteropancreatic reflex can also be activated by distension or administration of hyperosmolar solutions in the duodenum eliciting pancreatic enzyme secretion without raising plasma cholecystokinin levels. This effect is inhibited by atropine, suggesting that it is cholinergically mediated. Pancreatic response to duodenal volume or osmolality is not suppressed by trypsin, indicating that the reflex is not affected by intraluminal proteases. Our studies also show that secretion of pancreatic polypeptide is under cholinergic control, and this peptide acts by interfering with cholinergic transmission, making it an ideal candidate to modulate pancreatic secretion stimulated by the vagal cholinergic pathway. Similar observations are made with somatostatin and calcitonin-gene related peptide which also acts preferentially to inhibit pancreatic secretion by the vagal cholinergic pathway